2016
DOI: 10.1167/iovs.16-19758
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine Interleukin-6 and the Chemokines CCL20 and CXCL13 Are Novel Biomarkers of Specific Endogenous Uveitic Entities

Abstract: IL-6-driven immune responses are more potent in HLA-B27-associated uveitis and BD than in VKH disease, sarcoidosis, and IGU. CCL20 appears to be a specific biomarker of HLA-B27-associated uveitis, whereas CXCL13 appears to be a biomarker of VKH disease and IGU. Our findings suggest that IL-6, CCL20, and CXCL13 could serve as drug targets for treatment of specific clinical entities of endogenous uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 64 publications
2
34
0
1
Order By: Relevance
“…In the present study, we confirmed our previous data (Abu El‐Asrar et al. ) in a new set of AH samples with the use of another multiplex assay. Furthermore, the levels of CCL20 were elevated 465‐fold and 148‐fold in patients with HLA‐B27‐associated uveitis and BD, respectively, compared with controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we confirmed our previous data (Abu El‐Asrar et al. ) in a new set of AH samples with the use of another multiplex assay. Furthermore, the levels of CCL20 were elevated 465‐fold and 148‐fold in patients with HLA‐B27‐associated uveitis and BD, respectively, compared with controls.…”
Section: Discussionsupporting
confidence: 91%
“…; Abu El‐Asrar et al. ). The wide range in clinical manifestations and the varied response to therapy leave multiple challenges in uveitis management.…”
Section: Introductionmentioning
confidence: 99%
“…CCL17 also could be inhibited by overexpression of SOCS1 in the retina to regulate the recruitment of inflammatory cells [44]. The cytokine CCL20 was considered to be a specific biomarker of HLA-B27 -associated uveitis [45]. Our study revealed that CCL4 , CCL17 and CCL20 likely play essential roles in uveitis.…”
Section: Resultsmentioning
confidence: 85%
“…33 In the present study, the concentrations of CXCL13 in the AH were quantified in a new set of AH samples. The results were consistent with and confirmed our previous data in that higher concentrations of CXCL13 levels were measured in AH from patients with VKH disease.…”
Section: Discussionmentioning
confidence: 96%